Enhanced perfluorosulfonic acid proton exchange membrane batch preparation method and production line

By introducing a coating structure of sulfonated COFS and IL-Si dynamic crosslinking agent and UV/IR synergistic crosslinking technology into the perfluorosulfonic acid proton exchange membrane, the problems of membrane delamination and mechanical tension in the roll-to-roll process are solved, the self-healing ability and proton conductivity of the membrane are improved, and it is suitable for mass production.

CN121149320APending Publication Date: 2025-12-16DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511163215.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

Existing perfluorosulfonic acid proton exchange membranes have shortcomings in terms of mechanical durability and proton conductivity. In particular, they are prone to delamination and mechanical tension problems during roll-to-roll coating, which affect the lifespan and performance of fuel cells.

Method used

The coating structure, which combines sulfonated COFS with IL-Si dynamic crosslinking agent, provides a flexible framework through dynamic covalent bonds. Combined with UV and IR synergistic crosslinking technology, it forms ordered channels and a stable network, enhancing the self-healing ability and proton conductivity of the membrane. At the same time, after plasma treatment, a nano-SiO2 graft layer is formed to improve the interlayer bonding force.

Benefits of technology

It achieves stability and high proton conductivity of proton exchange membranes under mechanical tension in roll-to-roll processes, reduces delamination and cracks, improves the membrane's anti-swelling ability and self-healing efficiency, and meets the needs of mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121149320A_ABST
    Figure CN121149320A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, in particular to a batch preparation method and a production line of an enhanced perfluorosulfonic acid proton exchange membrane. The proton exchange membrane prepared by the invention comprises a perfluorosulfonic acid-based membrane, a double-sided grafting layer and a double-sided functional layer, the double-sided grafting layer comprises a perfluoroalkyl silane coupling agent containing nano silicon dioxide, and the double-sided functional layer comprises sulfonated COFs and an ionic liquid-containing functionalized siloxane dynamic cross-linking agent solution. After the base film is activated by Ar and O2 plasmas, the base film is coated with a perfluoroalkyl silane coupling agent containing hydroxylated nano SiO2, a covalent bond bridging layer is formed through hydrolytic condensation, the interlayer binding force is remarkably improved, crack propagation is inhibited, then UV and IR are subjected to synergistic cross-linking, a dual-function network of rapid curing and dynamic optimization is achieved, and the composite film is prepared. And in the roll-to-roll process, through double-sided asynchronous coating, thermal field induced crystallization and five-stage gradient annealing, the production line speed is matched, and the high flatness and swelling resistance of the membrane material are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of fuel cells, in particular to a batch preparation method and production line of enhanced perfluorosulfonic acid proton exchange membrane. BACKGROUND

[0002] As the core component of proton exchange membrane fuel cells (PEMFC) and water electrolysis hydrogen production (PEMWE), the proton exchange enhanced membrane (PEM) needs to meet the requirements of high proton conductivity, excellent chemical stability, high mechanical strength and long service life. The traditional single perfluorosulfonic acid-based membrane generally cannot meet the multi-performance requirements, for example, the problem of mechanical durability. Frequent dry-wet cycles cause the membrane to repeatedly swell / contract, causing mechanical stress, and cracks or perforations are prone to occur after long-term use, shortening the service life of the battery. Therefore, a large number of proton exchange enhanced membranes have emerged as the times require.

[0003] For batch preparation of proton exchange enhanced membrane, roll-to-roll coating (R2R) is one of the commonly used processes, which can realize high-speed continuous coating and greatly improve production efficiency. However, in the process of high-speed continuous coating, the interlayer of the material coating is more prone to delamination due to the problem of interfacial bonding force, and in the roll-to-roll batch preparation process, whether the coated coating on the base film can withstand the mechanical tension of the R2R production line is also a big challenge.

[0004] In summary, how to use the roll-to-roll coating process to prepare a proton exchange enhanced membrane that not only can withstand the mechanical tension of the R2R production line, but also can improve the delamination phenomenon in the coating process, and still maintain good basic properties such as proton conductivity and anti-swelling rate is one of the problems that need to be solved in the existing field of fuel cell proton exchange enhanced membrane preparation. SUMMARY

[0005] The purpose of the present application is to provide a preparation method of enhanced perfluorosulfonic acid proton exchange membrane and a batch preparation method thereof. The proton exchange membrane prepared by the method has good self-repairing ability, and also has good proton conductivity, anti-swelling rate, and can withstand the mechanical tension of the R2R production line and reduce the problem of interfacial bonding force.

[0006] In order to achieve the above-mentioned purpose, the technical scheme of the present application is as follows: The first aspect of the present application provides a preparation method of enhanced proton exchange membrane, comprising the following steps: Step 1, preparing functional slurry: a. mixing sulfonated COF S , amphiphilic block copolymer and solvent to obtain a sulfonated COFs dispersion after ultrasonic treatment; b. mixing the siloxane precursor with the ionic liquid containing double sulfonic acid groups, adding water, and hydrolyzing and condensing at pH = 3.5-4.5 and a temperature of 45-55℃ for 2-4h to obtain an IL-Si dynamic crosslinking agent solution; c. sulfonating the COF obtained in step a S to obtain a sulfonated COF mixing the dispersion liquid with the IL-Si dynamic crosslinking agent solution obtained in step b, and then adding perfluorosulfonic acid resin, nano cerium oxide, and ethylene glycol, and ultrasonically stirring until homogenization to obtain a functional slurry; Step 2: Plasma treating both sides of the perfluorosulfonic acid-based membrane, then immersing in a coupling agent solution and drying to form grafted layers on both sides of the perfluorosulfonic acid-based membrane; the coupling agent solution comprises perfluorooctyltriethoxysilane (PFOTES), surface-hydroxylated nano silicon dioxide, and a mixed solvent of ethanol and water; Step 3: Coating the functional slurry obtained in step 1 on the grafted layer on the first side of the perfluorosulfonic acid-based membrane, and sequentially performing thermal field-induced crystallization and ultraviolet light and infrared thermal field synergistic crosslinking to form a first functional layer; Step 4: Turning over the perfluorosulfonic acid-based membrane, coating the functional slurry of step 1 on the grafted layer on the second side of the perfluorosulfonic acid-based membrane, and sequentially performing thermal field-induced crystallization and ultraviolet light and infrared thermal field synergistic crosslinking to form a second functional layer;

[0007] In step a, the sulfonated COF S , the amphiphilic block copolymer, and the mixed solvent are in a mass ratio of 1: (0.01-0.1): (10-50); The sulfonated COF S is one of TpPa-SO3H and TpBD-(SO3H)2, wherein the pore size of the TpPa-SO3H is 1.2-1.8 nm, and the sulfonic acid group density is 3-4 mmol / g, and the pore size of the TpBD-(SO3H)2 is 1.8-2.4 nm, and the sulfonic acid group density is 2.8-3.6 mmol / g; The mixed solvent of DMSO and water is in a volume ratio of 1:1-1:3; The amphiphilic block copolymer is one of Pluronic F127 and PEO-PPO-PEO; The power of the ultrasonic is 400-600W, and the ultrasonic time is 20-40min; In step b, the molar ratio of the siloxane precursor to the ionic liquid containing double sulfonic acid groups is 1:2-1:4; The molar ratio of water to the siloxane precursor is 2-5:1; The siloxane precursor is one of TEOS and MTES; The double-sulfonic acid group-containing ionic liquid is one of 1,3-disulfonic acid group imidazolium hydrogen sulfate and 1,4-disulfonic acid group benzimidazolium phosphate; In step c, the molecular weight of the perfluorosulfonic acid resin is 800-2000 g / mol, and the sulfonation degree thereof is ≥1.2 meq / g.

[0008] The COF S The mass ratio of the dispersion liquid and the IL-Si dynamic crosslinking agent solution is 1:2-1:4. The concentration of the perfluorosulfonic acid resin in the functional slurry is 0.5-2 wt%, the concentration of the nano cerium oxide is 0.1-0.5 wt%, and the concentration of the ethylene glycol is 2-5 wt%.

[0009] The present application is further provided that, in step 2, the particle size of the surface-hydroxylated nano-silicon dioxide is 10-50 nm. In the mixed solvent, the volume ratio of ethanol and water is 9:1. In the coupling agent solution, the content of the surface-hydroxylated nano-silicon dioxide is 0.2-0.8 wt%, and the content of the perfluoroalkylsilane coupling agent is 1-3 wt%. The plasma treatment conditions are as follows: the working gas is a mixed gas of oxygen and argon at a volume ratio of 1:1, the flow rate is 50-200 mL / min, the treatment time is 30-180 s, and the treatment power is 60-120 W.

[0010] The present application is further provided that, in steps 3 and 4, the heat field-induced crystallization temperature is 80-100℃. The wavelength of the ultraviolet light is 254-385 nm, the power density is 50-200 mW / cm 2 , and the irradiation time is 30-120 s. The wavelength of the infrared light is 2.5-4 μm, the power density is 5-8 W / cm 2 , the irradiation temperature is 60-80℃, and the irradiation time is 2-3 min.

[0011] The present application is further provided that, in step 5, the gradient annealing conditions are as follows: the first stage annealing temperature is 80-100℃, the time is 5-8 min, the second stage annealing temperature is 110-120℃, the time is 8-12 min, the third stage annealing temperature is 130-140℃, the time is 6-10 min, the fourth stage annealing temperature is 100-110℃, the time is 5-8 min, and the fifth stage annealing temperature is 60-100℃, the time is 3-7 min.

[0012] The second aspect of the present application provides an enhanced proton exchange membrane prepared by the above preparation method, characterized by comprising a perfluorosulfonic acid-based membrane, a double-sided grafting layer and a double-sided functional layer. The double-sided grafting layer comprises surface-hydroxylated nanosilica and a perfluoroalkyl silane coupling agent, and the single-sided thickness is 0.5-2 μm. The double-sided functional layer comprises sulfonated COFs and an ionic liquid-containing functionalized siloxane dynamic crosslinker solution, and the single-sided thickness is 15-50 μm.

[0013] The third aspect of the present application provides a roll-to-roll production line used in the above preparation method, wherein the production line has a conveying mechanism comprising a base film unwinding roller, a base film winding roller and a conveying roller, and a plasma activation zone, a grafting immersion zone, a first coating zone, a first multi-temperature zone tunnel furnace, a first UV irradiation heating zone, a first infrared thermal field heating zone, a turning roller assembly, a second coating zone, a second multi-temperature zone tunnel furnace, a second UV irradiation heating zone, a second infrared thermal field heating zone and a gradient annealing zone are sequentially arranged between the base film unwinding roller and the base film winding roller along the conveying direction of the conveying mechanism. The plasma activation zone comprises a plasma treatment cavity, a vacuum pump for vacuumizing the plasma treatment cavity and a gas source pipeline for injecting gas into the plasma treatment cavity, and a pair of electrode plates parallel to the conveyed base film are arranged in the plasma treatment cavity and above and below the conveyed base film, respectively. The grafting immersion zone comprises an immersion tank and an oven. The first multi-temperature zone tunnel furnace and the second multi-temperature zone tunnel furnace both sequentially comprise an 80°C temperature zone and a 100°C temperature zone along the conveying direction of the conveying mechanism. The gradient annealing zone sequentially comprises a first temperature zone 80-100°C oven, a second temperature zone 110-120°C oven, a third temperature zone 130-140°C oven, a fourth temperature zone 100-110°C oven and a fifth temperature zone 60-100°C oven along the conveying direction of the conveying mechanism.

[0014] The fourth aspect of the present application provides a method for batch preparing an enhanced proton exchange membrane by using the above production line, comprising the following steps: S1, the perfluorosulfonic acid-based membrane is placed in the production line and tensioned and conveyed by the conveying mechanism, and the linear speed of the conveying mechanism is 1-2 m / min; S2, the perfluorosulfonic acid-based membrane is conveyed into the plasma treatment cavity for plasma treatment on the upper and lower surfaces of the perfluorosulfonic acid-based membrane; S3, a perfluoroalkyl silane coupling agent solution is prepared and placed in the impregnation tank of the grafting impregnation zone, and the temperature is controlled at 25-40°C, the perfluorosulfonic acid-based film is impregnated in the grafting impregnation tank under the transmission of the transmission mechanism and continuously transmitted for 10-15 min to achieve the grafting reaction, and then dried in an oven at 60-80°C in a vacuum environment for 10-15 min, thereby forming a grafting layer on both sides of the perfluorosulfonic acid-based film; S4, a functional slurry is prepared and placed in the feeding system of the first coating area and the second coating area, respectively, and the perfluorosulfonic acid-based film completed in S3 is transmitted to the first coating area under the transmission of the transmission mechanism, and the functional slurry is coated on the first grafting layer of the perfluorosulfonic acid-based film, the coating speed is 0.5-0.8 m / min, and then the first multi-temperature zone tunnel furnace is sequentially used for step-by-step drying at 80-100°C, thereby inducing layer-by-layer crystallization; S5, the film material after S4 is sequentially transmitted through the first UV irradiation heating area and the first infrared heat field heating area, and the coating layer is subjected to ultraviolet light and infrared heat field crosslinking, respectively, to form a first functional layer, wherein the ultraviolet light wavelength is 254-385 nm, the power density is 50-200 mW / cm 2 , the time is 30-120 s, the infrared wavelength is 2.5-4 μm, the power density is 5-8 W / cm 2 , the temperature is 60-80°C, and the time is 2-3 min; S6, the base film is turned over at the turning roller assembly, S4-S5 is repeated, the coating of the second side of the base film is completed, and a second functional layer is formed; S7, the film material after S6 is sequentially transmitted through the first temperature zone oven at 80-100°C, the second temperature zone oven at 110-120°C, the third temperature zone oven at 130-140°C, the fourth temperature zone oven at 100-110°C, and the fifth temperature zone oven at 60-100°C under the action of the transmission mechanism to perform gradient annealing, thereby obtaining an enhanced proton exchange membrane.

[0015] The application further provides that, in step S2, the specific steps of the plasma treatment are as follows: A, the perfluorosulfonic acid-based film is fixed on the transmission mechanism of the production line and transmitted to the plasma activation area; B, the vacuum pump of the plasma activation area is started to reduce the cavity pressure in the plasma treatment cavity to below 50 Pa; C, the mixed gas of Ar and O2 with a volume ratio of 1:1 is introduced into the plasma treatment cavity through the gas source pipeline, and the flow rate is 50-200 mL / min; D, the radio frequency power supply of the electrode plate is started to realize plasma excitation treatment on both sides of the perfluorosulfonic acid-based film, the treatment time is 30-180 s, and the treatment power is 60-120 W.

[0016] The application is further provided that, in step S7, annealing in the first temperature zone 80-100℃ oven for 5-8min; Annealing in the second temperature zone 110-120℃ oven for 8-12min; Annealing in the third temperature zone 130-140℃ oven for 6-10min; Annealing in the fourth temperature zone 100-110℃ oven for 5-8min; Annealing in the fifth temperature zone 60-100℃ oven for 3-7min.

[0017] The application has the following advantages: 1. The application adopts roll-to-roll process for the preparation of large quantities of proton exchange enhanced membranes. On the one hand, the functional coating layer of the application contains IL-Si dynamic crosslinking agent, which provides a flexible skeleton through dynamic covalent bonds, giving the membrane material elastic deformation ability. This structure allows the proton exchange enhanced membrane to locally reorganize dynamically when under stress, reducing the risk of brittle fracture. The UV and IR synergistic crosslinking used in the application can enhance the self-repairing efficiency, allowing the damaged area to heal quickly. Further, the nano-SiO2 in the double-sided grafting layer can inhibit crack propagation, effectively improve the bending resistance of the membrane and improve the water retention capacity. Therefore, the proton exchange enhanced membrane prepared by the application can well adapt to the mechanical tension of the R2R production line. In addition, the functional coating layer of the proton exchange enhanced membrane of the application contains sulfonated COF S structure, which can form COF S ordered channels, COF S rigid framework provides structural support, effectively resisting deformation during roll-to-roll transmission, and can automatically optimize cracks caused by mechanical tension, roll transmission and other factors in the roll-to-roll process, as well as the winding process of the R2R production line. On the other hand, the sulfonated COF S is mixed with the IL-Si dynamic crosslinking agent, and the two-dimensional covalent framework of the sulfonated COF S forms a rigid ordered structure through thermal field-induced crystallization, limiting the volume expansion of the coating layer after water absorption, reducing swelling deformation, and further combining IL-Si dynamic crosslinking to relieve thermal stress. Therefore, the proton exchange enhanced membrane has better membrane size stability; and the rigid skeleton of the COF S layer and the dynamic network of the IL-Si layer respectively inhibit the water absorption swelling on both sides of the base film, reducing the interlayer shear stress caused by the difference in swelling. At the same time, the sulfonated COF SWith ordered pores, forming continuous proton conduction path, the density of sulfonic acid group directly enhances the ability of proton dissociation and migration, and the IL-Si dynamic crosslinking agent containing ionic liquid with double sulfonic acid groups can provide additional proton carriers, and finally the COF S pores are arranged more orderly through heat field induced crystallization after coating, and the IL-Si dynamic crosslinking agent forms a stable network through UV and IR synergistic crosslinking, reducing the interference of micro defects on proton conduction, so that the sulfonated COF S in the functional coating of the present application and the IL-Si dynamic crosslinking network work together, combined with heat field induced crystallization and UV and IR synergistic crosslinking, can greatly and effectively improve the proton conduction efficiency, and alleviate the problem of proton conductivity decline caused by dehydration of perfluorosulfonic acid membrane at high temperature, and effectively improve the performance of fuel cell; In summary, the mixture of sulfonated COF S and IL-Si dynamic crosslinking in the functional coating of the present application can make the proton exchange enhanced membrane have good performance advantages in self-repairing, swelling inhibition and proton conduction, and at the same time has flexibility and dimensional stability of deformation resistance, so it is very suitable for mass production of proton exchange enhanced membrane roll-to-roll preparation process.

[0018] 2, The functional coating of the present application is provided with a grafting layer of perfluoroalkyl silane coupling agent, which is used to bridge the perfluorosulfonic acid based membrane and the functional coating, the perfluoroalkyl chain has high chemical compatibility with the base membrane, and the silane group forms a covalent bond with the surface of the base membrane through hydrolysis and condensation reaction, which can significantly enhance the interlayer bonding force and prevent peeling, a small amount of surface hydroxylated nano silicon dioxide can be uniformly dispersed in the grafting layer through the interaction between the surface hydroxyl group and the silane coupling agent, increase the rigidity of the coating and inhibit crack propagation, further improve the overall mechanical strength of the proton exchange enhanced membrane, and the rigid network of nano SiO2 can also limit the volume expansion of the grafting layer after water absorption, combined with gradient annealing process, further stabilize the microstructure and reduce the influence of environmental humidity change on the performance of the proton exchange enhanced membrane; 3, The present application performs plasma treatment on both sides of the perfluorosulfonic acid based membrane, the hydrophilicity of the activated double sides is enhanced through low temperature plasma, and then a solution of surface hydroxylated nano silicon dioxide perfluoroalkyl silane coupling agent is sprayed to form a grafting layer, wherein the perfluoroalkyl silane coupling agent can form a uniform film on the surface of the base membrane through spraying, so as to balance the surface wettability, make the subsequent functional slurry evenly spread and stably adhere, and reduce the risk of interface delamination; 4, The present application adopts UV and IR synergistic crosslinking to rapidly cure the dynamic network, the siloxane group in the IL-Si dynamic crosslinking agent can be excited by UV light to promote photosensitive hydrolysis and condensation reaction, and quickly form a crosslinking network skeleton, and then fix the sulfonated COF SIR can promote the flow of ionic liquid phase microdomains in the IL-Si dynamic crosslinking agent, repair local defects, and the two can realize the staged reaction of "rapid curing + dynamic optimization", compared with the traditional single thermal crosslinking process, the film forming time is significantly shortened, so this way can adapt and match the production line speed of the roll-to-roll process, effectively break through the process bottleneck of continuous dynamic crosslinking; In addition, the dynamic crosslinking reaction assisted by infrared heat field can adapt to temperature fluctuations, so that the film maintains a stable network structure under different working conditions; In addition, UV and IR synergistic crosslinking avoids the risk of COF S structure collapse caused by single high temperature treatment, and the synergistic effect of ordered channels and ionic liquid double sulfonic acid groups ensures stable proton conductivity; 5、The process of the present application finally sets a five-stage gradient annealing treatment, the first temperature zone of 80-100 DEG C is a preheating stage to ensure the preliminary volatilization of the solvent; The second temperature zone of 110-130 DEG C is a main drying zone to accelerate solvent removal; The third temperature zone of 140-150 DEG C is a crosslinking strengthening zone to promote molecular chain crosslinking; The fifth temperature zone of 110-130 DEG C is a slow cooling zone to avoid warping caused by sudden cooling and eliminate internal stress; The fifth temperature zone of 100-60 DEG C is a final cooling zone to ensure stable product output; The present application controls the molecular structure of the coating by precise stage thermodynamic control + dynamic parameter adaptation, accurately matches the phase change of the material, realizes directional solvent removal, and realizes deep crosslinking and stress release, thereby effectively improving the mechanical strength, interface stability and weather resistance; 6、The first surface and the second surface are coated with functional slurry, then induced by multi-temperature zone gradient heat field, the molecular chains are relaxed and oriented layer by layer, forming long-range ordered ion cluster channels to improve proton conductivity, and the gradual temperature rise can also avoid microcracks caused by sudden heating, improving the flatness of the film surface; And after the first surface and the second surface are coated with functional slurry, UV and IR are used for synergistic interface strengthening, ultraviolet light constructs a dynamic disulfide bond crosslinking network on the surface to give self-repairing ability, and also improves wear resistance, infrared heating excites the C-F bond vibration of the functional layer, promotes chemical anchoring with the catalyst layer, strengthens the interfacial bonding force, and inhibits interlayer peeling during fuel cell operation. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 The structure schematic diagram of the production line in Example 4 is shown in the figure. In the figure: 1, base film unwinding roller; 2, plasma activation zone; 2-1, plasma treatment cavity; 2-2, vacuum pump; 2-3, gas source pipeline, 2-4, electrode plate; 3, grafting immersion zone, 3-1, immersion pool, 3-2, oven; 4, first coating zone; 5, first multi-temperature zone tunnel furnace, 5-1, 80°C temperature zone, 5-2, 100°C temperature zone; 6, first UV irradiation heating zone; 7, first infrared thermal field heating zone; 8, turning roller assembly; 9, second coating zone; 10, second multi-temperature zone tunnel furnace; 10-1, 80°C temperature zone; 10-2, 100°C temperature zone; 11, second UV irradiation heating zone; 12, second infrared thermal field heating zone; 13, gradient annealing zone; 13-1, first temperature zone 80-100°C oven; 13-2, second temperature zone 110-120°C oven; 13-3, third temperature zone 130-140°C oven; 13-4, fourth temperature zone 100-110°C oven; 13-5, fifth temperature zone 60-100°C oven; 14, base film winding roller; Figure 2 Figure of the swelling phenomenon of the proton exchange membrane of Comparative Example 1. DETAILED DESCRIPTION

[0020] The application will be further described in detail below with reference to the accompanying drawings.

[0021] Example 1 Step 1, preparation of functional slurry a. Take 10 g of TpPa-SO3H with a sulfonic acid group density of 4 mmol / g and a pore size of 1.2 nm, 1 g of Pluronic F127, and dissolve them in a mixed solvent of 500 g of DMSO and water (135 g of DMSO + 365 g of water), ultrasonic for 40 min at a power of 600 W, centrifugal to remove undispersed particles, and obtain sulfonated COF S dispersion; b. Mix 1 mol of TEOS with 4 mol of 1,3-disulfonic acid imidazolium hydrogen sulfate, add 4 mol of water, adjust pH to 4.5, and hydrolyze and condense at 55°C for 4 h to obtain an IL-Si dynamic crosslinker solution; c. Take 100 g of the COF S dispersion of step 1 and mix with 400 g of the IL-Si dynamic crosslinker solution of step 2, add 10 g of perfluorosulfonic acid resin (molecular weight 2000 g / mol, sulfonation degree 1.5 meq / g), 2.5 g of nano cerium oxide, and 25 g of ethylene glycol, ultrasonic stirring until homogenization, to obtain a functional slurry; Step 2, the perfluorosulfonic acid-based film is placed in a plasma treatment chamber and a mixed gas of Ar and O2 in a volume ratio of 1:1 is introduced into the plasma treatment chamber at a flow rate of 200 mL / min, and the radio frequency power supply of the electrode plate is started to achieve plasma excitation treatment of the upper and lower surfaces of the perfluorosulfonic acid-based film for 180 s, during which the power is 120 W. 6 g of SiO2 with a particle size of 50 nm and a surface hydroxylated (Evonik OX50) is mixed with 25 g of PFOTES and 1000 ml of an ethanol solution (900 ml of ethanol + 100 ml of water) to form a mixed solution. Then, the perfluorosulfonic acid-based film after plasma treatment is immersed in the mixed solution for 10 min, and dried at 80°C for 20 min to form a grafted layer with a thickness of 1.8 μm on both surfaces of the perfluorosulfonic acid-based film. Step 3, functional slurry is coated on the grafted layer on the first surface of the perfluorosulfonic acid-based film, and then heat field induction treatment is performed, i.e. the film material is placed in an oven, heated from 80°C to 100°C at a rate of 3°C / min, and dried for 12 min. The film material is irradiated with UV light with a wavelength of 385 nm and an energy density of 200 mW / cm 2 for 120 s, and then irradiated with IR light with a wavelength of 4 μm, a power density of 8 W / cm 2 , and a temperature of 80°C for 3 min to complete the crosslinking, obtaining a first functional layer with a thickness of 50 μm. Step 4, the second surface is coated by the method of step 3 after being turned over, and a second functional layer with a thickness of 50 μm is obtained. Step 5, the film material after step 4 is subjected to gradient annealing treatment, including a first stage (preheating stage) at a temperature of 100°C for 8 min, a second stage (main drying stage) at a temperature of 120°C for 12 min, a third stage (crosslinking strengthening stage) at a temperature of 140°C for 10 min, a fourth stage (slow cooling stage) at a temperature of 110°C for 8 min, and a fifth stage (final cooling stage) at a temperature of 100°C for 7 min, obtaining an enhanced proton exchange membrane.

[0022] Example 2 Step 1, preparation of functional slurry a. 10 g of TpPa-SO3H with a sulfonic acid group density of 3 mmol / g and a pore size of 1.8 nm, 0.5 g of PEO-PPO-PEO, are dissolved in 300 g of a DMSO and water mixed solvent (100 g of DMSO + 200 g of water), and ultrasonic treatment is performed at a power of 500 W for 30 min. After centrifugation to remove undispersed particles, a sulfonated COF S dispersion is obtained. b. Mix 1 mol MTES with 3 mol 1,4-disulfonate benzimidazolium phosphate, add 3.5 mol water, adjust pH = 4.0, hydrolysis and condensation at 50°C for 3h to obtain IL-Si dynamic crosslinking agent solution; c. Take 100g of step 1 COF S Mix the dispersion with 300g of step 2 IL-Si dynamic crosslinking agent solution, add 5g of perfluorosulfonic acid resin (molecular weight 1500 g / mol, sulfonation degree 1.3 meq / g), 1.5g of nano cerium oxide, 14g of ethylene glycol, and ultrasonic stirring until homogenization to obtain a functional slurry; Step 2, place the perfluorosulfonic acid-based membrane in a plasma treatment chamber and introduce a mixed gas of Ar and O2 in a volume ratio of 1:1 into the plasma treatment chamber at a gas flow rate of 125 mL / min, and start the radio frequency power supply of the electrode plate to achieve plasma excitation treatment of the upper and lower surfaces of the perfluorosulfonic acid-based membrane for 100s. During this process, the power is 90 W. Mix 5g of 30nm particle size surface hydroxylated SiO2 (Cabot CAB-O-SIL L-90), 20g of PFOTES, and 1000ml of ethanol solution (900ml of ethanol + 100ml of water) to form a mixed solution. Then, immerse the plasma-treated perfluorosulfonic acid-based membrane in the mixed solution for 15min, dry at 70°C for 18min, and then form a grafted layer with a thickness of 1.2μm on both sides of the perfluorosulfonic acid-based membrane; Step 3, coat the functional slurry on the first side of the perfluorosulfonic acid-based membrane, then perform thermal field induction treatment, i.e. place the membrane in an oven, heat from 80°C to 100°C at a rate of 4°C / min, and dry for 10min. Use UV light with a wavelength of 365 nm and an energy density of 100 mW / cm 2 UV irradiate the membrane for 80s, then use IR with a wavelength of 3μm, a power density of 6 W / cm 2 , and a temperature of 70°C to irradiate the membrane for 2.5min to complete the crosslinking, obtaining a first functional layer with a thickness of 30μm; Step 4, flip over and coat the second side using the method of step 3, and obtain a second functional layer with a thickness of 30μm; Step 5, perform gradient annealing treatment on the membrane completed in step 4, with the first stage (preheating stage) at a temperature of 90°C for 6.5min, the second stage (main drying stage) at a temperature of 115°C for 10min, the third stage (crosslinking strengthening stage) at a temperature of 135°C for 8min, the fourth stage (slow cooling stage) at a temperature of 105°C for 6.5min, and the fifth stage (final cooling stage) at a temperature of 80°C for 5min, obtaining an enhanced proton exchange membrane.

[0023] Example 3 Step 1, preparation of functional slurry a. Take 10 g of TpBD-(SO3H)2 with a sulfonic acid group density of 3.6 mmol / g and a pore size of 1.8 nm, 1 g of Pluronic F127, and dissolve them in a mixed solvent of 100 g of DMSO and water (50 g of DMSO + 50 g of water), ultrasonic for 40 min at a power of 400 W, centrifugal to remove undispersed particles, and obtain sulfonated COF S dispersion; b. Mix 1 mol of TEOS with 2 mol of 1,3-disulfonic acid imidazolium hydrogen sulfate, add 2.5 mol of water, adjust the pH to 3.5, and hydrolyze and condense at 45°C for 2 h to obtain an IL-Si dynamic crosslinking agent solution; c. Take 100 g of the COF S of step 1, mix it with 200 g of the IL-Si dynamic crosslinking agent solution of step 2, add 2.5 g of perfluorosulfonic acid resin (molecular weight 800 g / mol, sulfonation degree 1.2 meq / g), 0.5 g of nano cerium oxide, and 6 g of ethylene glycol, and ultrasonic stirring until homogenization to obtain a functional slurry; Step 2, the perfluorosulfonic acid-based film is placed in a plasma treatment chamber, a mixed gas of Ar and O2 with a volume ratio of 1:1 is introduced into the plasma treatment chamber, the gas flow is 50 mL / min, and the radio frequency power of the electrode plate is started to achieve plasma excitation treatment on the upper and lower surfaces of the perfluorosulfonic acid-based film for 30 s, the power is 60 W during the process, 2 g of surface hydroxylated SiO2 with a particle size of 10 nm (Evonik AEROSIL® 300), 10 g of PFOTES, and 1000 ml of an ethanol solution (900 ml of ethanol + 100 ml of water) are mixed to form a mixed solution, and the temperature is controlled at 30°C, then the plasma-treated perfluorosulfonic acid-based film is immersed in the mixed solution for 12 min, and after drying at 70°C for 18 min, a grafted layer with a thickness of 0.8 μm is formed on both surfaces of the perfluorosulfonic acid-based film; Step 3, functional slurry is coated on the grafted layer on the first surface of the perfluorosulfonic acid-based film, and then heat field induction treatment is performed, i.e. the film material is placed in an oven, the temperature is raised from 80°C to 100°C at a rate of 2°C / min, and dried for 8 min, the film material is irradiated with UV light with a wavelength of 254 nm and an energy density of 50 mW / cm 2 for 30 s, and then the film material is irradiated with IR light with a wavelength of 2.5 μm, a power density of 5 W / cm 2 , and a temperature of 60°C for 2 min to complete the crosslinking, and a first functional layer with a thickness of 15 μm is obtained; Step 4, flip and coat the second surface by the method of step 3, and obtain a second functional layer with a thickness of 15 μm; Step 5, the film material of completion 4 is subjected to gradient annealing treatment, respectively, first stage (preheating stage), temperature 80℃, time 5min, second stage (main drying stage), temperature 110℃, time 8min, third stage (crosslinking strengthening stage), temperature 130℃, time 10min, fourth stage (slow cooling stage), temperature 100℃, time 5min, fifth stage (final cooling stage), temperature 60℃, time 3min, to obtain the enhanced proton exchange membrane.

[0024] Example 4 The embodiment provides a roll-to-roll production line for batch preparation of an enhanced proton exchange membrane, the production line has a conveying mechanism, including a base film unwinding roller, a base film winding roller and a conveying roller, located between the base film unwinding roller and the base film winding roller and arranged in the conveying direction of the conveying mechanism in sequence as a plasma activation zone, a grafting and impregnation zone, a first coating zone, a first multi-temperature zone tunnel furnace, a first UV irradiation heating zone, a first infrared heat field heating zone, a turning roller assembly, a second coating zone, a second multi-temperature zone tunnel furnace, a second UV irradiation heating zone, a second infrared heat field heating zone, and a gradient annealing zone. The plasma activation zone comprises a plasma treatment cavity, a vacuum pump for vacuumizing the plasma treatment cavity, and a gas source pipeline for injecting gas into the plasma treatment cavity; the plasma treatment cavity is provided with a pair of electrode plates parallel to the conveyed base film and arranged above and below the conveyed base film, respectively. The grafting and impregnation zone comprises an impregnation tank and an oven. The first multi-temperature zone tunnel furnace and the second multi-temperature zone tunnel furnace are both arranged in sequence as 80℃ temperature zone and 100°C temperature zone along the conveying direction of the conveying mechanism. The gradient annealing zone comprises, in sequence along the conveying direction of the conveying mechanism, a first temperature zone 100℃ oven, a second temperature zone 120℃ oven, a third temperature zone 140℃ oven, a fourth temperature zone 110℃ oven, and a fifth temperature zone 100℃ oven.

[0025] Example 5 The embodiment provides a method for batch preparation of an enhanced proton exchange enhanced membrane by using the production line of the embodiment 4, and the specific steps are as follows: S1, the perfluorosulfonic acid base film is placed in the production line and subjected to tension type conveying by the conveying mechanism, and the linear speed of the conveying mechanism is 1m / min; S2, the perfluorosulfonic acid base film is conveyed into the plasma treatment cavity, the vacuum pump of the plasma activation zone is started, the cavity pressure in the plasma treatment cavity is reduced to below 50 Pa, Ar and O2 mixed gas is introduced into the plasma treatment cavity through the gas source pipeline, the gas flow is 200 mL / min, and the radio frequency power supply of the electrode plate is started to realize the plasma excitation treatment of the upper and lower surfaces of the perfluorosulfonic acid base film for 180s, and the power is 120 W during the process. S3, according to the manner of preparing the perfluoroalkyl silane coupling agent solution in step 2 of embodiment 1: take 0.6 kg of 50 mm particle size surface hydroxylated SiO2 (Evonik OX50), 2.5 kg of PFOTES, and 100 L of ethanol solution (90 L of ethanol + 10 L of water) to form a mixed solution, and then load the mixed solution into the impregnation tank of the grafting impregnation zone. The perfluorosulfonic acid-based film is conveyed into the impregnation tank under the action of the conveying mechanism, and the film is impregnated for 10 min while being conveyed. Then, the film is dried in an 80° oven for 20 min to complete the silane coupling agent grafting reaction, and a 1.8 μm grafting layer is formed on both sides of the perfluorosulfonic acid-based film; S4, scale up the functional slurry prepared in step 1 of embodiment 1 by 100 times, and then place the slurry in the feeding system of the first coating area and the second coating area (a. take 1 kg of TpPa-SO3H with a sulfonic acid group density of 4 mmol / g and a pore size of 1.2 nm, 100 g of Pluronic F127, dissolve in 50 kg of DMSO and water mixed solvent (13.5 kg of DMSO + 36.5 kg of water), ultrasonic for 40 min under the power of 600 W, centrifugal to remove the undispersed particles, and obtain the sulfonated COFs dispersion; b. mix 100 mol of TEOS with 400 mol of 1,3-bis-sulfonic acid imidazole hydrogen sulfate, add 350 mol of deionized water, adjust the pH to 4.5, and hydrolyze and condense at 55°C for 4 h to obtain the IL-Si dynamic crosslinking agent solution; c. mix 10 kg of the COFs dispersion obtained in step a with 40 kg of the I-Si dynamic crosslinking agent solution obtained in step b, add 1 kg of perfluorosulfonic acid resin (molecular weight 2000 g / mol, sulfonation degree 1.5 meg / g), 250 g of nano cerium oxide, and 2.5 kg of ethylene glycol, and ultrasonic stir until homogenization to obtain the functional slurry), and the perfluorosulfonic acid-based film after S3 is conveyed to the first coating area under the action of the conveying mechanism, and the functional coating is coated on the grafting layer of the first side of the film material at a coating speed of 0.5 m / min. Then, the film material is sequentially dried at 80°C and 100°C for 12 min in the first multi-temperature zone tunnel furnace, and the process is used to induce crystallization layer by layer to obtain a functional coating with a thickness of 50 μm; S5, the film material after S4 is sequentially conveyed through the first UV irradiation heating zone and the first infrared heat field heating zone, and is subjected to ultraviolet light (UV) and infrared heat field (IR) synergistic crosslinking to form a first functional layer; the wavelength of the ultraviolet light is 385 nm, the power density is 200 mW / cm 2 , the time is 120 s, the infrared wavelength is 4 μm, the power density is 5 kW / m 2 , the temperature is 80°C, and the time is 3 min; S6, the base film is turned over at the turning roller assembly, and the second side is coated according to the steps of S4-S5 to form a second functional layer; S7, the film material after S6 is sequentially subjected to each temperature zone of the gradient annealing zone under the action of the conveying mechanism, and is respectively annealed in the first temperature zone 100°C oven for 8 min (preheating stage), the second temperature zone 120°C oven for 12 min (main drying stage), the third temperature zone 140°C oven for 10 min (cross-linking strengthening stage), the fourth temperature zone 110°C oven for 8 min (slow cooling stage), and the fifth temperature zone 100°C oven for 7 min (final cooling stage) to obtain the enhanced proton exchange membrane.

[0026] Comparative Example 1 Referring to the preparation steps and parameter formula of Example 5, the difference is that no sulfonated COF is added. S That is, the preparation method of the functional slurry is changed to: 10 g of perfluorosulfonic acid resin with a molecular weight of 2000 g / mol and a sulfonation degree of 1.5 meq / g, 2.5 g of nano cerium oxide, and 25 g of ethylene glycol are added to 400 g of IL-Si dynamic crosslinking agent, and the mixture is stirred and ultrasonically mixed until homogeneous to obtain the required functional slurry. Then, the functional slurry is fed into the feeding system of the first coating zone and the second coating zone of S4 in Example 5.

[0027] Comparative Example 2 Referring to the preparation steps and parameter formula of Example 5, the difference is that no IL-Si dynamic crosslinking agent solution is contained, that is, the preparation method of the functional slurry is changed to: 1. 10 g of sulfonated TpPa-SO3H with a sulfonic acid density of 2 mmol / g, a pore size of 3 nm, and a surface covalently modified with hydroxyl groups, 1 g of Pluronic F127 dispersant, and 500 g of DMSO and water mixed solvent (125 g of DMSO + 375 g of water) are dissolved. Ultrasonic for 40 min at 600 W power, centrifugation, COF S COF with a particle size of 180 nm S dispersion liquid; 2. 10 g of perfluorosulfonic acid resin with a molecular weight of 2000 g / mol and a sulfonation degree of 1.5 meq / g, 2.5 g of nano cerium oxide, and 25 g of ethylene glycol are added to 100 g of the COF dispersion liquid of step 1, and the mixture is stirred and ultrasonically mixed until homogeneous to obtain the required functional slurry. Then, the functional slurry is fed into the feeding system of the first coating zone and the second coating zone of S4 in Example 5.

[0028] Comparative Example 3 Referring to the preparation steps and parameter formula of Example 5, the difference is that there is no plasma treatment and grafting layer, that is, the steps of plasma activation and silane coupling agent spraying in Example 5 are omitted, and the functional slurry is directly coated on the base film.

[0029] Comparative Example 4 Referring to the preparation steps and parameter formulations of Example 5, the difference is that no perfluorosulfonic acid resin transition agent, nano cerium oxide and ethylene glycol are added, that is, the preparation method of the functional slurry is changed as follows: 100 g of the COFs dispersion liquid of step 1 is mixed with 400 g of the IL-Si dynamic crosslinking agent of step 2 to obtain the required functional slurry by ultrasonic stirring until homogenization; the remaining steps are the same, and then the sample is loaded into the loading system of the first coating area and the second coating area of S4 of Example 5.

[0030] Comparative Example 5 Referring to the preparation steps and parameter formulations of Example 5, the difference is that the stepless temperature rising area is cancelled, that is, after the functional coating is coated on the grafted layer of the first surface and the second surface of the film material of Example 5 S4, it is directly dried at 120°C constant temperature, and the remaining steps are unchanged.

[0031] Comparative Example 6 Referring to the preparation steps and parameter formulations of Example 5, the difference is that there is no UV and IR crosslinking process, that is, the step of Example 5 S5 is cancelled, and the remaining steps are unchanged.

[0032] Comparative Example 7 Referring to the preparation steps and parameter formulations of Example 5, the difference is that the gradient annealing linear temperature rising is changed, that is, S7 is changed as follows: after S6 is completed, the film material is sequentially passed through each temperature zone of the gradient annealing area under the action of the conveying mechanism, which are respectively 80°C oven annealing for 8 min in the first temperature zone, 120°C oven annealing for 12 min in the second temperature zone, and 140°C oven annealing for 10 min in the third temperature zone, and the remaining steps are unchanged.

[0033] The above Examples 1-3 and Comparative Examples 1-7 are subjected to performance testing: the sample is placed in a constant temperature and humidity box (80°C, 30% RH) for 24 h until swelling equilibrium, and then the sample is quickly taken out, the size is measured within 30 s to detect the swelling rate; the proton conductivity is obtained by using an electrochemical workstation by means of alternating current impedance spectroscopy (EIS); a standard scratch (depth ≈ 50% of film thickness, length 1 cm) is made on the film surface with a microscopic blade; the damaged sample is placed in a self-repairing condition (80°C, 90% RH) for 24 h, and then the tensile strength before and after repair is tested, and the self-repairing efficiency = damage amount / repair amount × 100%; the sample is pressed with a pet protective film, and a universal material testing machine is used to perform 180° peeling at a speed of 10 mm / min, and the peeling force F (N) is recorded, and the interfacial bonding strength (N / cm) is calculated; a universal material testing machine is used to stretch at a constant speed until fracture, and the force-displacement curve is recorded in real time, and the tensile strength (MPa) is calculated. The test results are shown in Table 1.

[0034] Table 1

[0035] As can be seen from Table 1: Comparative Examples 1, 3, and 4 performed poorly in terms of swelling rate: Comparative Example 1 lacked sulfonated COF. S The rigid skeleton cannot suppress water absorption and swelling (such as...) Figure 2 (As shown); In Comparative Example 3, the nano-SiO2 in the grafted layer can limit water absorption and swelling, and the swelling rate increases significantly after its absence; In Comparative Example 4, due to the absence of perfluorosulfonic acid resin transition agent, the coating has poor compatibility with the base film and is prone to delamination and swelling after water absorption.

[0036] Comparative Examples 1 and 5 showed poor performance in terms of proton conductivity: In Comparative Example 1, the ordered channels of COFs are the main pathway for proton conduction. When these channels are missing, the proton conduction relies only on the ionic liquid phase of IL-Si, resulting in a significant decrease in conductivity. In Comparative Example 5, direct high-temperature drying caused the COFs channels to become disordered, which would hinder proton migration.

[0037] Comparative Examples 2, 6, and 7 showed poor self-healing capabilities: In Comparative Example 2, the IL-Si dynamic crosslinking agent is the core of the self-healing network, and its absence prevents the formation of dynamic covalent bonds; In Comparative Example 6, UV light can excite the siloxane groups in the IL-Si dynamic crosslinking agent, promoting photosensitive hydrolysis and condensation reactions and rapidly constructing the crosslinking network framework, while the infrared thermal field promotes the flow of ionic liquid micro-regions through thermal excitation, repairing local defects. Without this process, the dynamic crosslinking network cannot be fully formed, resulting in a significant decrease in self-healing function; Comparative Example 7 (linear annealing): Without segmented stress relief, the crosslinking network is incomplete, and the self-healing efficiency is reduced.

[0038] In Comparative Example 1, due to the lack of COF S The sulfonated covalent organic framework is the core supporting structure of the self-healing network. Its ordered channels provide anchoring sites for the IL-Si dynamic crosslinking agent. (The missing COF...) S At that time, IL-Si cannot form a stable dynamic covalent bond network, so the self-healing function in Comparative Example 1 cannot be activated; The grafted layer forms covalent bonds with the base film through a perfluoroalkylsilane coupling agent and disperses nano-SiO2 to inhibit crack propagation. In Comparative Example 3, when the grafted layer is missing, the functional coating and the base film rely solely on physical adsorption, and the interface is easily peeled off, resulting in the instability of the dynamic network.

[0039] Comparative Examples 1, 3, and 4 showed poor performance in terms of interfacial adhesion: COF in Comparative Example 1 SThe rigid skeleton of the coating can enhance the mechanical anchoring of the coating and the base film, and the adhesion decreases after the absence; due to the plasma activation, the surface of the base film is etched and polar groups are introduced, which can improve the hydrophilicity of the perfluorosulfonic acid base film, if the step is absent, the surface of the base film remains hydrophobic and low surface energy, thus the subsequent functional slurry cannot be uniformly spread, interface voids are formed, and the adhesion is reduced, and the silane coupling agent forms a covalent bond with the surface of the base film through hydrolysis and condensation reaction, and its perfluoroalkyl chain is chemically compatible with the base film, which plays a role of "molecular bridge", when the grafting layer is absent, the base film and the functional coating only rely on physical adsorption, lack of chemical bonding, and easy to peel off due to mechanical stress or swelling difference, therefore, in the comparative example 3, the plasma activation and the silane coupling agent grafting are the key steps to form covalent bond, and the interface adhesion will decrease significantly after the absence; in the comparative example 4, the perfluorosulfonic acid resin transition agent can improve the chemical compatibility of the coating and the base film, and the delamination risk will increase after the absence.

[0040] The mechanical properties and the performance of the roll-to-roll are poor in the comparative examples 3, 5 and 7: the nano-SiO2 in the grafting layer can inhibit crack propagation, the tensile strength will decrease in the comparative example 3 after the absence, thus the roll-to-roll production line tension cannot be adapted; in the comparative example 5, the mechanical strength decreases due to the rapid heating and the micro-cracks, and the film material is easy to break during the roll-to-roll transmission; in the comparative example 7, the stress is not released in segments, the film material warping risk increases, and the winding flatness is affected.

[0041] The specific embodiments are only an explanation of the present application, and are not a limitation of the present application, and the person skilled in the art can make modifications to the embodiments without creative contribution according to the needs after reading the specification, but as long as the modifications are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A method for preparing an enhanced proton exchange membrane, characterized in that, Includes the following steps: Step 1, Prepare the functional slurry: a. Sulfonated COF S An amphiphilic block copolymer and a solvent were mixed and ultrasonicated to obtain a sulfonated COF dispersion. b. Mix the siloxane precursor with an ionic liquid containing disulfonic acid groups, add water, and hydrolyze and condense at pH=3.5-4.5 and temperature 45-55℃ for 2-4 hours to obtain an IL-Si dynamic crosslinking agent solution. c. The sulfonated COF obtained in step a S The dispersion was mixed with the IL-Si dynamic crosslinking agent solution obtained in step b, and then perfluorosulfonic acid resin, nano-cerium oxide and ethylene glycol were added. After ultrasonic stirring until homogenization, the functional slurry was obtained. Step 2: Plasma treatment is performed on both sides of the perfluorosulfonic acid-based membrane, followed by immersion in a coupling agent solution and drying to form a graft layer on both sides of the perfluorosulfonic acid-based membrane; the coupling agent solution includes perfluorooctyltriethoxysilane, surface-hydroxylated nano-silica, and a mixed solvent of ethanol and water. Step 3: The functional paste obtained in Step 1 is coated on the first grafted layer of the perfluorosulfonic acid base film, and then subjected to thermal field-induced crystallization and synergistic cross-linking by ultraviolet light and infrared thermal field to form the first functional layer. Step 4: The functional paste from Step 1 is coated onto the second graft layer of the perfluorosulfonic acid-based membrane, and then subjected to thermal field-induced crystallization and synergistic cross-linking by ultraviolet light and infrared thermal field to form the second functional layer. Step 5: Perform gradient annealing on the membrane material obtained in Step 4 to obtain the enhanced proton exchange membrane.

2. The preparation method according to claim 1, characterized in that: In step a, the sulfonated COF S The mass ratio of the amphiphilic block copolymer to the mixed solvent is 1: (0.01-0.1): (10-50). The sulfonated COF S It is one of TpPa-SO3H and TpBD-(SO3H)2, wherein the pore size of TpPa-SO3H is 1.2-1.8 nm and the sulfonic acid group density is 3-4 mmol / g, and the pore size of TpBD-(SO3H)2 is 1.8-2.4 nm and the sulfonic acid group density is 2.8-3.6 mmol / g; The solvent is a mixture of DMSO and water in a volume ratio of 1:1 to 1:3; The amphiphilic block copolymer is one of Pluronic F127 and PEO-PPO-PEO; The power of the ultrasound is 400-600W, and the duration of the ultrasound is 20-40 minutes. In step b, the molar ratio of the siloxane precursor to the ionic liquid containing disulfonic acid groups is 1:2 to 1:

4. The molar ratio of water to siloxane precursor is 2-5:1; The siloxane precursor is one of TEOS and MTES; The ionic liquid containing disulfonic acid groups is one of 1,3-disulfonic acid imidazolium hydrogen sulfate and 1,4-disulfonic acid benzimidazolium phosphate; In step c, the molecular weight of the perfluorosulfonic acid resin is 800-2000 g / mol, and its degree of sulfonation is ≥1.2 meq / g. The COF S The mass ratio of the dispersion to the IL-Si dynamic crosslinking agent solution is 1:2 to 1:4; The functional slurry contains 0.5-2 wt% perfluorosulfonic acid resin, 0.1-0.5 wt% nano-cerium oxide, and 2-5 wt% ethylene glycol.

3. The preparation method according to claim 1, characterized in that: In step 2, the particle size of the surface-hydroxylated nano-silica is 10-50 nm; In the mixed solvent, the volume ratio of ethanol to water is 9:1; In the coupling agent solution, the content of surface-hydroxylated nano-silica is 0.2-0.8 wt%, and the content of perfluoroalkylsilane coupling agent is 1-3 wt%. The plasma treatment conditions are as follows: the working gas is a mixture of oxygen and argon in a volume ratio of 1:1, the flow rate is 50-200 mL / min, the treatment time is 30-180 s, and the treatment power is 60-120 W. Immerse in the coupling agent solution for 10-15 minutes, then dry at 60-80℃.

4. The preparation method according to claim 1, characterized in that: In steps 3 and 4, the temperature for thermally induced crystallization is 80-100℃; The ultraviolet light has a wavelength of 254-385nm and a power density of 50-200 mW / cm². 2 The irradiation time is 30-120 seconds; Infrared light wavelength 2.5-4μm, power density 5-8 W / cm² 2 Irradiation temperature 60-80℃, irradiation time 2-3min.

5. The preparation method according to claim 1, characterized in that: In step 5, the gradient annealing conditions are as follows: first stage annealing temperature 80-100℃, time 5-8min; second stage annealing temperature 110-120℃, time 8-12min; third stage annealing temperature 130-140℃, time 6-10min; fourth stage annealing temperature 100-110℃, time 5-8min; and fifth stage annealing temperature 60-100℃, time 3-7min.

6. An enhanced proton exchange membrane prepared by the preparation method according to any one of claims 1-5, characterized in that: Includes perfluorosulfonic acid-based membrane, double-sided grafted layer, and double-sided functional layer; The double-sided grafted layer includes a perfluoroalkyl silane coupling agent containing surface-hydroxylated nano-silica, with a single-sided thickness of 0.5-2 μm; The double-sided functional layer comprises sulfonated COFs and a dynamic crosslinking agent solution containing ionic liquid functionalized siloxane, with a single-sided thickness of 15-50 μm.

7. A roll-to-roll production line used in the preparation method according to any one of claims 1-5, characterized in that: The production line has a conveying mechanism, which includes a base film unwinding roller, a base film take-up roller, and a conveying roller located between the base film unwinding roller and the base film take-up roller. Along the conveying direction of the conveying mechanism, the roller is sequentially configured as a plasma activation zone, a grafting impregnation zone, a first coating zone, a first multi-temperature zone tunnel furnace, a first UV irradiation heating zone, a first infrared thermal field heating zone, a steering roller assembly, a second coating zone, a second multi-temperature zone tunnel furnace, a second UV irradiation heating zone, a second infrared thermal field heating zone, and a gradient annealing zone. The plasma activation zone includes a plasma processing chamber, a vacuum pump for evacuating the plasma processing chamber, and a gas source pipe for injecting gas into the plasma processing chamber. The plasma processing chamber is provided with a pair of electrode plates parallel to the base film being transported, and they are respectively placed above and below the base film being transported. The grafting impregnation area includes an impregnation tank and an oven; Both the first multi-temperature zone tunnel furnace and the second multi-temperature zone tunnel furnace are sequentially 80°C and 100°C temperature zones along the conveying direction of the conveying mechanism. The gradient annealing zone includes, in sequence along the conveying direction of the conveying mechanism, a first temperature zone of 80-100℃ oven, a second temperature zone of 110-120℃ oven, a third temperature zone of 130-140℃ oven, a fourth temperature zone of 100-110℃ oven, and a fifth temperature zone of 60-100℃ oven.

8. A method for batch preparation of enhanced proton exchange membranes using the production line described in claim 7, characterized in that, Includes the following steps: S1. The perfluorosulfonic acid-based film is placed in the production line and is tensioned and conveyed by a conveyor mechanism with a linear speed of 1-2 m / min. S2. The perfluorosulfonic acid membrane is transferred to the plasma processing chamber for plasma treatment of both the upper and lower surfaces of the perfluorosulfonic acid membrane. S3. Prepare a perfluoroalkylsilane coupling agent solution and place it in the impregnation tank of the grafting impregnation area. Control the temperature to 25-40°C. The perfluorosulfonic acid base membrane is impregnated in the grafting impregnation tank under the conveying mechanism and continuously conveyed for 10-15 minutes to achieve the grafting reaction. Then, it is dried in an oven at 60-80°C under vacuum for 10-15 minutes to form a graft layer on both the upper and lower surfaces of the perfluorosulfonic acid base membrane. S4. Prepare the functional slurry and place it in the feeding system of the first coating zone and the second coating zone respectively. The perfluorosulfonic acid base film completed in S3 arrives at the first coating zone under the conveying mechanism. The functional slurry is coated on the first graft layer of the perfluorosulfonic acid base film at a coating speed of 0.5-0.8 m / min. Then, it is dried in stages at 80-100°C in the first multi-temperature zone tunnel furnace to induce layer-by-layer crystallization. S5. After completing S4, the membrane material is sequentially conveyed through the first UV irradiation heating zone and the first infrared thermal field heating zone. The coating layer undergoes ultraviolet light and infrared thermal field cross-linking to form the first functional layer, wherein the ultraviolet light wavelength is 254-385nm and the power density is 50-200 mW / cm². 2 Duration: 30-120 seconds; Infrared wavelength: 2.5-4 μm; Power density: 5-8 W / cm² 2 Temperature 60-80℃, time 2-3 minutes; S6. The base film is flipped at the steering roller assembly, and S4-S5 are repeated to complete the coating of the second side of the base film and form the second functional layer. S7. After completing S6, the membrane material is sequentially annealed in the following ovens under the action of the conveying mechanism: the first temperature zone 80-100℃ oven, the second temperature zone 110-120℃ oven, the third temperature zone 130-140℃ oven, the fourth temperature zone 100-110℃ oven, and the fifth temperature zone 60-100℃ oven, to obtain an enhanced proton exchange membrane.

9. The method according to claim 8, characterized in that: In step S2, the specific steps of plasma treatment are as follows: A. The perfluorosulfonic acid-based film is fixed on the conveyor mechanism of the production line and conveyed to the plasma activation zone; B. Start the vacuum pump in the plasma activation zone to reduce the pressure in the plasma processing chamber to below 50 Pa; C. Introduce a 1:1 mixture of Ar and O2 gas into the plasma processing chamber through a gas source pipe at a flow rate of 50-200 mL / min. D. Start the radio frequency power supply of the electrode plate to achieve plasma excitation treatment on both sides of the perfluorosulfonic acid-based film. The treatment time is 30-180s and the treatment power is 60-120 W.

10. The method according to claim 8, characterized in that: In step S7, annealing is performed in an oven at 80-100℃ in the first temperature zone for 5-8 minutes; Anneal in the second temperature zone of the oven at 110-120℃ for 8-12 minutes; Anneal in the third temperature zone 130-140℃ oven for 6-10 minutes; Anneal in an oven at 100-110℃ in the fourth temperature zone for 5-8 minutes; Anneal in the fifth temperature zone 60-100℃ oven for 3-7 minutes.